TANFIDH BIR AL-WĀLIDAIN FI TAFĀ’ULĀT AL-IJTIMĀ’IYAH LI MUJTAMA’ MADURA: Tahlīl Thaqāfat Abhakte min Manzūr Al-Tarbiyah Al-Islamiyah (JOURNAL OF INDONESIAN ISLAM, 2025)
This article aims to determine the concept, practice, and results of abhkate, a good attitude toward parents of Madurese society from Islamic education perspective. This study utilizes a qualitative approach, employing data collection methods such as interviews, observations, and document analysis. The data were analyzed through a process that includes reduction, presentation, verification, and the formulation of conclusions. Conceptually, abhakte is a translation of the concept of birr al-walidayn in Islam. Forms of abhakte in Madurese culture include: andhap asor, mabhunga, ajhaga bhagussa, nyambhung bhala, majar otang, sandhekka, amoljaaghi, dhuwa'aghi, and mintaaghi sapora. Madurese society strives to maintain the abhakte culture by practicing: ngajhi gik anak (learning Islam from an early age), nyantre (learning in Islamic boarding school education), ebada (religious rituals), and kabiyasaan sabhalaan (family traditions). Meanwhile, the results of the implementation of abhakte in the social interactions of Madurese society include: koko agamana (strong adherence to Islamic teachings), taretan sadhaja (organized in a family structure), sangkolan bhagus (maintaining good traditions in society), tonggal dara (strengthening a sense of togetherness), and akor salanjhanga (minimizing the risk of social conflict).